METHANOL EXTRACT PROFILE OF Eucheuma cottonii AS AN ANTIMALARIAL CANDIDATE - Setyaningrum, Endah; Farisi, Salman; Sari, Galuh Retno; Arifiyanto, Achmad (JURNAL PENA SAINS, 2024)
Malaria is a tropical disease that endangers public health which is caused by the plasmodium parasite, and transmitted through the bite of a female Anopheles sp. mosquito. Malaria is a major health problem in Indonesia due to its high risk of transmission and drug resistance. This encourages a study to look for other antimalarial alternatives by utilizing natural ingredients. The purpose of this study is to identify the functional groups found in Eucheuma cottonii secondary metabolites using methanol 70% as the solvent. This study is included in the experimental research. The functional group of methanol extract of Eucheuma cottonii was evaluated using Fourier Transform Infrared (FT-IR) Nicolet iS 10 spectrometers. The FT-IR analysis identified the O-H functional group at 3347.1 cm-1, C≡C at 2094.8 cm-1, C=C at 1632.6 cm-1, phenol or O-H bend at 1401.5 cm-1, aromatic C-O at 1192.7 cm-1, and a C-C group at 1043.7 cm-1. The results of phytochemical analysis on Eucheuma cottoni revealed the presence of saponins. The functional groups formed in the 70% methanol extract of Eucheuma cottonii seaweed are the O-H, C≡C, C=C, phenol or O-H bend, aromatic C-O, and C-C groups which are flavonoid compounds in the flavanone group which have the potential to be antimalarial. Furthermore, the presence of the O-H, C=O, C-O, C=C, or C-H functional groups is a characteristic of a flavonoid compound. Therefore, it can be concluded that the identified functional groups indicate the existence of flavonoid molecules from the flavanone group, which potential as antimalarial properties.